Analysis Of Language Politiety In Youtube Content Tonightshow Vindest-Andika - Amelia Barus; Khanaya Shalsabilla; Vina Agustina; Achmad Yuhdi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to analyze language politeness in conversations in Vindest-Andika's tonighshow YouTube videos. This type of research uses a descriptive method with a qualitative approach. The data collection technique in this research uses note-taking and listening techniques. politeness of language in Vindest's YouTube Talkshow content can be concluded that there are several maxims that exist in the conversation between Vindest and Andika, namely the maxim of wisdom which occurs at minutes 7.12 and 18.46, the maxim of generosity which occurs at minutes 6.23 and 23.14, the maxim of appreciation which occurs at minutes 24.34 , the simplicity maxim which occurs at minutes 1.19 and 14.55, the consensus maxim which occurs at 2.48 and 11.15 minutes and finally the sympathy maxim which occurs at 5.22 and 15.35 minutes..